Transcriptome and Metabolome Reprogramming in Tomato Plants by Trichoderma harzianum strain T22 Primes and Enhances Defense Responses Against Aphids - Coppola, Mariangela; Diretto, Gianfranco; Digilio, Maria Cristina; Woo, Sheridan Lois; Giuliano, Giovanni; Molisso, Donata; Pennacchio, Francesco; Lorito, Matteo; Rao, Rosa (Frontiers in Physiology, 2019)
Beneficial fungi in the genus Trichoderma are among the most widespread biocontrol agents of plant pathogens. Their role in triggering plant defences against pathogens has been intensely investigated, while, in contrast, very limited information is available on induced barriers active against insects. The growing experimental evidence on this latter topic looks promising, and paves the way towards the development of Trichoderma strains and/or consortia active against multiple targets. However, the predictability and reproducibility of the effects that these beneficial fungi is still somewhat limited by the lack of an in-depth understanding of the molecular mechanisms underlying the specificity of their interaction with different crop varieties, and on how the environmental factors modulate this interaction. To fill this research gap, here we studied the transcriptome changes in tomato plants (cultivar “Dwarf San Marzano”) induced by Trichoderma harzianum (strain T22) colonization and subsequent infestation by the aphid Macrosiphum euphorbiae. A wide transcriptome reprogramming, related to metabolic processes, regulation of gene expression and defence responses, was induced both by separate experimental treatments, which showed a synergistic interaction when concurrently applied. The most evident expression changes of defence genes were associated with the multitrophic interaction Trichoderma-tomato-aphid. Early and late genes involved in direct defence against insects were induced (i.e. peroxidase, GST, kinases and polyphenol oxidase, miraculin, chitinase), along with indirect defence genes, such as sesquiterpene synthase and geranylgeranyl phosphate synthase. Targeted and untargeted semi-polar metabolome analysis revealed a wide metabolome alteration showing an increased accumulation of isoprenoids in Trichoderma treated plants. These data nicely fit with the higher mortality of aphids when feeding on Trichoderma treated plants, herein reported, and with the previously observed attractiveness of these latter towards the aphid parasitoid Aphidius ervi. Moreover, Trichoderma treated plants showed the over-expression of transcripts coding for several families of defence-related transcription factors (bZIP, MYB, NAC, AP2-ERF, WRKY), suggesting that the fungus contributes to the priming of plant responses against pest insects. Collectively, our data indicate that Trichoderma treatment of tomato plants induces transcriptomic and metabolomic changes, which underpin both direct and indirect defence responses.